Development of new generation of vaccines for Brucella abortus. Issue 12 (December 2018) - Gheibi, Azam; Khanahmad, Hossein; Kashfi, Khosrow; Sarmadi, Mahdieh; Khorramizadeh, Mohammad Reza
Abstract: Brucella abortus is a Gram-negative facultative and intracellular bacteria, it causes bovine brucellosis, a zoonotic disease that is responsible for considerable economic loss to owners of domesticated animals and can cause problems in otherwise healthy humans. There are a few available live attenuated vaccines for animal immunization against brucellosis; however, these have significant side effects and offer insufficient protective efficacy. Thus, the need for more research into the Molecular pathobiology and immunological properties of B. abortus that would lead to the development of better and safer vaccines. In this paper we have reviewed the main aspects of the pathology and the responsive immunological mechanisms, we have also covered current and new prospective vaccines against B. abortus .